God is red : the secret story of how Christianity survived and flourished in Communist China - Liao, Yiwu, 1958- (New York : HarperOne, 2011)
When journalist Liao Yiwu first stumbled upon a vibrant Christian community in the officially secular China, he knew little about Christianity. In fact, he'd been taught that religion was evil, and that those who believed in it were deluded, cultists, or imperialist spies. But as a writer whose work has been banned in China and has even landed him in jail, Liao felt a kinship with Chinese Christians in their unwavering commitment to the freedom of expression and to finding meaning in a tumultuous society. Unwilling to let his nation lose memory of its past or deny its present, Liao set out to document the untold stories of brave believers whose totalitarian government could not break their faith in God, including: The over-100-year-old nun who persevered in spite of beatings, famine, and decades of physical labor, and still fights for the rightful return of church land seized by the government; The surgeon who gave up a lucrative Communist hospital administrator position to treat villagers for free in the remote, mountainous regions of southwestern China; The Protestant minister, now memorialized in London's Westminster Abbey, who was executed during the Cultural Revolution as "an incorrigible counterrevolutionary." This ultimately triumphant tale of a vibrant church thriving against all odds serves as both a powerful conversation about politics and spirituality and a moving tribute to China's valiant shepherds of faith, who prove that a totalitarian government cannot control what is in people's hearts.
The trip to Dali. The cemetery -- The old nun -- The Tibetan -- The elder (I) -- The Episcopalian -- The cancer patient -- The fellowship -- The Yi and Miao villages. The doctor -- The martyr -- The elder (II) -- The Yi minister -- The feast -- Beijing and Chengdu. The secret visit -- The underground minister -- The poet and the priest -- The blind musician -- The orphanage -- The new convert.
Keywords: Communism and Christianity -- China -- History -- 20th century; Communism and Christianity -- China -- History -- 21st century; China -- Church history -- 20th century; China -- Church history -- 21st century